The Effect of Profitability, Leverage and Company Size on Intellectual Capital Disclosure (2019-2021 Non-Cyclical Company Sector) - Mohamad Zulman Hakim; Choirun Nisa Azizah; Basuki Basuki; Reni Anggraeni; Sri Yanto; Daniel Rahandri (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the effect of profitability, leverage and firm size on intellectual capital disclosure in the non-cyclical sector of the company in 3 years of observation (2019-2021). The population used in this study were 111 companies and the return of the sample was purposive sampling technique and produced 44 samples of companies. Based on the results of multiple linear regression analysis (t- test), it can be concluded that profitability has no effect on intellectual capital disclosure, leverage has no effect on intellectual capital disclosure and firm size has no effect on intellectual capital disclosure